(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Employability is a set of skills, qualities, and accomplishments that improve graduates’ chances of landing jobs and succeeding in their chosen fields, which benefits the person, the workforce, the community, and the economy. Therefore, employability refers to a larger variety of talents and attributes that will allow a person to succeed throughout their working life and go beyond simply being able to find a job. Someone who recently earned their college or university diploma is referred to as a new graduate. After graduating from a variety of schools and universities around the world, thousands of students majoring in hospitality hunt for employment each year. Others are employed by the employer during the campus placement period, while some of them find employment on their own. Unfortunately, some of them get turned down. Employability skills are highly valued by employers because they are far more difficult to teach than job-specific abilities. Some employable traits are innate, while others can be learned through training, employment, or regular practice. Even though they may not be mentioned in a job description, employability skills are crucial and can increase your appeal to potential employers. The biggest advantage of possessing these qualities is that they might make you stand out from other job applicants who are vying for the same position. The BSHM graduates should possess the performance skills to collaborate with others, especially during times of high demand. They should be able to interact with others effectively through speaking, writing, and body language. They must be able to adapt quickly when unexpected events arise at work. Graduates of the BSHM program should be able to demonstrate and adapt leadership. They have to develop time management skills so that they may concentrate on taking things one step at a time. Whenever making a choice, they must carefully consider their opinion.